The School Garden: A Social and Emotional Place - Pollin, Susan; Retzlaff-Fürst, Carolin (Frontiers in Psychology, 2021)
School gardens are part of many schools. Especially in primary schools, but also in secondary schools, they are used as a learning space and experience space for the pupils. Their importance for the development of cognitive and emotional-affective abilities of the pupils is empirically well proven. It is also empirically well proven that exposure to nature has an influence on the prosocial behavior of children and adults. But there is a lack of studies to investigate the effect of the stay in the school garden on the social behavior of the pupils in secondary class. To investigate whether school garden is a good environment for social learning, a questionnaire-study and standardized observations were carried out. These observations were made on sixth grade pupils during a 90-minute class, in the school garden as well in the classroom. Over a period of ten weeks, the pupils (31 girls and 22 boys) changed weekly between the garden and the room. Over 150 observations were held in the school garden (82) and in the classroom (68). In summary, pupils show more socially competent behavior in school garden lessons than in the classroom. The school garden, designed according to the basic needs, seems to create favorable incentives for social learning. Due to the frequent social interactions, it can be assumed that activities in school gardens can promote emotional and social competence.